Hierarchical bismuth oxychlorides constructed by porous nanosheets: Preparation, growth mechanism, and application in photocatalysis. (March 2015) - Sun, Dongfeng; Wang, Tingyu; Xu, Yaohui; Li, Ruixing; Sato, Tsugio
Abstract: Hierarchical structures bismuth oxychlorides (BiOCl) were synthesized via a solvothermal process assisted with citric acid using methanol as a solvent. The as-synthesized hierarchical structures were constructed by porous nanosheets. The crystal growth and morphology structures of BiOCl were significantly influenced by the amount of citric acid, the solvothermal time and the solvent used in reaction. Based on the electron microscope observations, the growth of such hierarchitectures has been proposed as an Ostwald ripening process followed by self-assembly. Pore-size distribution analysis revealed that both mesopores and macropores existed in the product. UV–vis spectroscopy was employed to estimate the band gap energies and light utilization efficiency of the BiOCl hierarchical structures. Moreover, the adsorption capability and photocatalytic activities of BiOCl hierarchical structures were evaluated on the degradation of rhodamine B and methyl orange under either UV light or simulated sunlight illumination, respectively. The results assumed that BiOCl hierarchical structures sample showed much higher photocatalytic activity than the conventionally prepared sample and commercial TiO2 (Degussa, P25).